Urgensi Pengembangan Ruang Terbuka Hijau di Kota Bandung dalam Upaya Mewujudkan Kota Layak Anak : Urgency of Developing Bandung’s Green Open Spaces to Protect Children’s Right to a Healthy Environment - Alifa Putriana; Ikhwan Aulia Fatahillah (Faculty of Law, Maranatha Christian University, 2025)
Abstract This article is written based on issues concerning the right to a healthy living environment through the development of Green Open Spaces and their relation to the concept of child-friendly cities. Every individual, regardless of background, is entitled to the right to a good and healthy environment. One of the key efforts to realize this right is to ensure the availability and proper development of Green Open Spaces. It would be much better if the green open spaces in every city were equipped with facilities that can support children's growth and development, especially in the city of Bandung which is currently on its way to becoming a Child-Friendly City. Based on empirical legal methods using primary sources and secondary ones obtained through literature research and interviews, the city of Bandung has not yet met the criteria for child-friendly green open spaces due to the lack of green open spaces equipped with children's play facilities as an effort to support children's growing process and development both educationally and psychologically. The necessity of providing green open spaces, such as city parks, with designs that consider the developmental stages of children, aims to create a comfortable and safe play environment for them, in order to realize Bandung City as a Child-Friendly City and to fulfil the right to a good and healthy living environment, as reflected in Article 65 (1) of Law Number 32 of 2009 on Environmental Protection and Management.